Improving Students’ Speaking Skills Through Describing Picture Strategy at SMP Negeri 7 Palu - Devitriani AR. Haku; Abdul Kamaruddin; Mashuri Mashuri; Hastini Hastini (MASI Mandiri Edukasi, 2026)
Descriptive speaking skills remain among the most challenging competencies for junior high school students, particularly in contexts where English is taught as a foreign language. Many students struggle with pronunciation, fluency, vocabulary, and comprehensibility, resulting in limited confidence and difficulty expressing descriptive information. This study aims to determine the effectiveness of the Describing Picture Strategy in developing the descriptive speaking skills of eighth-grade students at SMP Negeri 7 Palu. Using a quasi-experimental design with a pretest–posttest control group, the study involved 57 students selected through simple random sampling. The experimental group received treatment using the Describing Picture Strategy, while the control group received conventional instruction. Data were collected using a speaking performance test and analyzed through descriptive and inferential statistics using SPSS 25. The results show a significant improvement in the experimental group’s mean score from 59.69 to 71.81, compared to the control group’s increase from 58.24 to 61.08. An Independent Samples T-Test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between the groups. These findings demonstrate that the Describing Picture Strategy effectively enhances students' pronunciation, fluency, and comprehensibility by providing visual stimuli that trigger ideas and reduce speaking anxiety. The study concludes that visual-based, student-centered techniques are beneficial for improving descriptive speaking performance in EFL contexts.